ANALISIS KONTRIBUSI SEKTOR PERTANIAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - Tri, Mita (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2019)
This study aims to find out the contribution of agriculture sector towards the Product Domestic Regional Bruto (PDRB) in the Berau regency. Under the guidance of Dr.H.Muhammad Bayu, Drs.MM as the first supervisor and Mr. Dandy Ahmad Drajad, S.Sos.Msi as the second supervisor. The aims of this study is to find out the percentage contribution  of agriculture sector towards Product Domestic Regional Bruto (PDRB) in the Berau regency. This study use secondary data within annual years form or time series from 2013 until 2017 which obtainable from Badan Pusat Statistik (BPS) in the Berau Regency. Result of this study indicate that every years the contribution of agriculture sector always increase, however always stand under ten percent. In 2017 the contribution of agriculture sector indicate the bigger number than four years latest in 2013-2016. It?s beacause of goverment program for development agriculture and plantation sector and the demand of agriculture result to shipped.